Clinically depressed and typically developing mother–infant dyads: Domain base rates and correspondences, relationship contingencies and attunement. (3rd August 2021) - Bornstein, Marc H.; Manian, Nanmathi; Henry, Lauren M.
Abstract: Maternal depression is associated with adverse outcomes in infants. Unfavorable parenting practices likely constitute one pathway of risk transmission from mother to infant, but definitional and methodological variation in the extant literature precludes a comprehensive or conclusive understanding of potential underlying mechanisms. This study aimed to illuminate the role of maternal clinical depression in mother–infant interaction by turning a microanalytic lens on four substantive relationship issues: base rates, correspondences, contingencies, and attunement. Several maternal parenting practices (aggregated into social, didactic, and language domains) and several infant behaviors (aggregated into social, exploration, and non‐distress vocalization domains) were microcoded to 0.10 s from naturalistic hour long interactions of clinically depressed mothers ( n = 60) and matched non‐depressed controls ( n = 60) with their 5‐month‐olds. Clinically depressed mothers spontaneously engaged their infants less didactically, were less contingent to their infants in social, didactic, and language domains, and were less attuned with their infants than were non‐depressed mothers. Infants of clinically depressed mothers vocalized non‐distress less than infants of non‐depressed mothers. These differences unveil key disadvantages in the everyday lived experiences of infants of clinically depressed mothers. The findings advance understanding of maternal depression and its effects and have implications for identifying infants at risk on account of their mothers' clinical depression.